Comparative safety and effectiveness of rivaroxaban versus VKAs in patients with venous thromboembolism - Sindet-Pedersen, Caroline; Pallisgaard, Jannik Langtved; Staerk, Laila; Gerds, Thomas Alexander; Fosbøl, Emil Loldrup; Torp-Pedersen, Christian; Gislason, Gunnar; Olesen, Jonas Bjerring (Thrombosis and Haemostasis, 2017)
The approval of rivaroxaban has changed the landscape of treatment of venous thromboembolism (VTE). Little is known about the effect of rivaroxaban compared with vitamin K antagonists (VKA), when used in the everyday clinical practice. The aim of this study was to investigate the safety and effectiveness of rivaroxaban compared with VKAs among patients with VTE, using the Danish nationwide registries. All patients diagnosed with VTE and treated with either rivaroxaban or VKAs between 2013 and 2015 were included. A total of 12,318 patients were diagnosed with VTE and treated with VKAs [n=6,907] or rivaroxaban [n=5,411.]. Combined Cox regression analyses showed that the standardised absolute six-month risk of recurrent VTE was 3.03 % [95 % CI: 2.57 % to 3.48 %] in the rivaroxaban group and 3.13 % [95 % CI: 2.70 % to 3.56 %] in the VKA group (absolute risk difference of –0.11 % [95 % CI: –0.76 % to 0.54 %]). The standardised absolute six-months risk of bleeding was 2.28 % [95 % CI: 1.87 % to 2.67 %] for patients in the rivaroxaban group and 2.10 % [95 % CI: 1.78 % to 2.43 %] in the VKA group (absolute risk difference of 0.18 % [95 % CI: –0.34 % to 0.67]). In conclusion, rivaroxaban was associated with similar risk of recurrent VTE and bleeding compared with VKA.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Venous thromboembolism; anticoagulation; vitamin K antagonists; rivaroxaban; non-vitamin K antagonist oral anticoagulants